Pathology of Extrinsic Ligaments: A Pictorial Essay - Shahabpour, Maryam; Van Overstraeten, Luc; Ceuterick, Paul; Milants, Annemieke; Goubau, Jean; Boulet, Cedric; De Mey, Johan; De Maeseneer, Michel (Seminars in Musculoskeletal Radiology, 2012)
The role of the extrinsic ligaments, together with the intrinsic ligaments, appears to be much more important than previously thought in the setting of carpal stability. The anatomy and pathology of the extrinsic wrist ligaments is complex. Magnetic resonance imaging (MRI) with thin slices is essential for visualization. This article describes the pathological appearance of the extrinsic palmar and dorsal radiocarpal and ulnocarpal ligaments on MRI, correlated with arthroscopy (performed by two skilled hand surgeons), clinical findings, and follow-up. High-resolution MRI, especially using isotropic three-dimensional sequences with orthogonal multiplanar reconstructions on 3T MR systems, allows detailed depiction of many of the extrinsic ligaments affected in carpal injuries. Recognition of ligament abnormalities is improved by intra-articular or intravenous injection of contrast before the examination. Both techniques may help to determine the precise localization, size, and extent of dorsal and palmar radiocarpal and ulnocarpal ligament lesions. Further experience with these techniques is needed to define the place of MRI in the management of traumatic wrist injuries.
Keywords: MRI; extrinsic ligaments; wrist; carpal instability; 3T